2017
DOI: 10.1111/cdev.12947
|View full text |Cite
|
Sign up to set email alerts
|

Parental Autonomy Support in Two Cultures: The Moderating Effects of Adolescents’ Self‐Construals

Abstract: Parental autonomy support has been related to positive adolescent outcomes, however, its relation to outcomes in collectivist cultural groups is unclear. This study examined relations of specific autonomy supportive behaviors and outcomes among 401 adolescents (M = 12.87) from the United States (N = 245) and collectivist-oriented Ghana (N = 156). It also examined whether adolescents' self-construals moderated the relations of specific types of autonomy support with outcomes. Factor analyses indicated two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 58 publications
4
76
1
1
Order By: Relevance
“…Thus, the respondents with low SES might have reported low life satisfaction possibly because of the direct physiological effects of lack of financial and material resources, which may inform, for example, poor shelter and inadequate material assets considering that the study participants were selected from the poorest region in Ghana. The finding that those with high social capital have high life satisfaction could also be linked to the socioemotional support derived from a sense of belonging, autonomy support, and control [34,35]. It was again found in this study that those with high social capital were more likely to feel happier compared to those with low social capital even after adjustments.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Thus, the respondents with low SES might have reported low life satisfaction possibly because of the direct physiological effects of lack of financial and material resources, which may inform, for example, poor shelter and inadequate material assets considering that the study participants were selected from the poorest region in Ghana. The finding that those with high social capital have high life satisfaction could also be linked to the socioemotional support derived from a sense of belonging, autonomy support, and control [34,35]. It was again found in this study that those with high social capital were more likely to feel happier compared to those with low social capital even after adjustments.…”
Section: Discussionsupporting
confidence: 65%
“…It is, hence, probable that the respondents assessed their life satisfaction based on their material conditions while they assessed their happiness based on their psychosocial conditions-social capital. The positive relationship between social capital and happiness can also be linked to the psychological benefits such as self-esteem and self-worth which is derived from a sense of belonging, autonomy, and control [34,35]. This study, moreover, found that autonomy support and control are crucial for the wellbeing of adolescents in a collectivist society-Ghana [28,34].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our results indicating lack of culture moderation are inconsistent with the results of some studies showing that the effects of several aspects of parental autonomy support and control are culturally sensitive (e.g., Marbell-Pierre, et al, 2017;Qin et al, 2009;Soenens et al, 2015). For example, Qin et al (2009) found that decision-making autonomy predicted enhanced emotional functioning more in the United States than in China.…”
Section: Discussioncontrasting
confidence: 99%
“…While SDT's basic premises (Ryan & Deci, 2017) suggest that parental temperament-insensitivity is likely to undermine sense of autonomy and intrinsic motivation in most children, it is important to consider factors that may moderate these negative effects. Thus, in line with recent conceptualizations and research anchored in SDT (e.g., Marbell-Pierre, Grolnick, Stewart, & Raftery-Helmer, 2017;Soenens, Vansteenkiste, & Van Petegem, 2015) and research on autonomy in adolescence (e.g., Qin, Pomeratnz, & Wang, 2009), stressing the potential effects of cultural contexts, it seems important to start examining whether the negative effects of parental insensitivity to children's temperament dispositions are moderated, perhaps even canceled, by some cultural backgrounds. Research examining this issue is important because, if the negative effects of temperament-insensitivity will emerge across widely different cultures, this may suggest that temperament-sensitivity is a fundamental aspect of autonomy support.…”
Section: Introductionmentioning
confidence: 78%